Ti/Pt/TiO2 electrodes prepared by DC Magnetron Sputtering: Environmental application on the degradation of the Acid Orange 7 - Serio,Susana (2017)
Titanium dioxide electrodes were prepared in three stages: (i) electrodeposition of Pt layer on a Ti substrate that was (ii) covered by a TiO2 thin film deposited by DC Magnetron Sputtering technique, at constant pressure of 0.8 Pa and oxygen partial pressure of 0.08 Pa, and (iii) annealed at 400 °C. The structural (XRD) characterization of the films was performed, showing a predominant anatase-TiO2 phase, where some peaks corresponding to the Ti/Pt substrate were also observed. The average crystallite size for the films was 44 nm, showing the nanocrystalline nature of these anatase-TiO2 films. The surface morphology of the films was studied by scanning electron microscopy and revealed agglomerates of nanosized grains or particulates, distributed over the substrate surface with a 'blooming flower-like' appearance. The nanosized grains result in an increase in active surface area and also promote the formation of porous TiO2 films. The performance of Ti/Pt/TiO2 as anode was evaluated in the electrodegradation of an azo dye, the acid orange 7 (AO7). Assays were run at 0.1, 0.25 and 1 mA cm-2, using AO7 concentration of 50 mg L-1, and after 12 h assays colour (484 nm) and chemical oxygen demand removals up to 97 and 70% were obtained, respectively. The energetic yield decreased with the increase in current density, which is typical from a process controlled by diffusion. The platinization of the substrate improves the adhesion of the TiO2 film, increasing its lifetime, and increases the conductivity of the films, decreasing the energetic costs of the process.